EFEKTIFITAS MEDIA RUMAT TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN DATAR KELAS IV DI MI TERPADU AL-FALAH BAKALAN KALINYAMATAN JEPARA - Herwin Widyatmoko; Saidatul Irfana; Kholida Firdausia; Latifathun Nikmah (Tunas Nusantara, 2019)
This study aims to describe the effectiveness of learning media “RUMAT” in Mathematics subject specifically about plane materials for elementary school students grade IV. The type of this study is experimental study. The subjects of this study are students and teachers in grade IV MI Terpadu Al-Falah, Bakalan, Kalinyamatan, Jepara. The students were divided into two groups: experimental group and control group. Students in experimental group were taught about plane material using “RUMAT” media while students in control group were taught about the same material without using the media. In the end of the study, post test was done in order to know if there is difference result from both groups. The data in this study is about The Effectiveness of RUMAT as A Learning Media to Teach Plane Materials on Mathematics Subject for Students Grade IV in MI Terpadu Al-Falah, Bakalan, Kalinyamatan, Jepara. Some techniques such observation, interview, documentation, and test were done to collect the data. The result of T-test on experimental and control groups is 2,041. The finding from T-test shows that Tcount > Ttable or 2,041 > 1,673 which means that Ho is refused and Ha is accepted. From the data mentioned above, it can be concluded that the use of “RUMAT” is effective to be used as a learning media to teach plane material for students grade IV in MI Terpadu Al-Falah, Bakalan, Kalinyamatan, Jepara.Keywords: RUMAT media, learning outcome